2013
DOI: 10.1111/irv.12136
|View full text |Cite
|
Sign up to set email alerts
|

Influenza research in the Eastern Mediterranean Region: the current state and the way forward

Abstract: We searched published literature, surveillance data sources, and sequence databases to analyze the state of influenza virus research and to identify research gaps in the World Health Organization (WHO) Eastern Mediterranean Region. PubMed, Scopus, and other databases were searched for influenza publications and nucleotide sequences. WHO's FluNet was searched to determine virologic reporting from each country. We found that influenza research has increased in recent years with the emergence of H5N1 and pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
0
20
1
Order By: Relevance
“…Once more, we observed a higher prevalence among studies conducted in rural populations versus urban populations. A recent study conducted in 2010 reported an HCV prevalence of 8.7% among children with viral hepatitis [87]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Once more, we observed a higher prevalence among studies conducted in rural populations versus urban populations. A recent study conducted in 2010 reported an HCV prevalence of 8.7% among children with viral hepatitis [87]. …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, HCV prevalence among adult diabetic patients was 20.0% [100] and 60.3% [111]. Substantial HCV prevalence was also observed among patients attending hospitals, ranging between 0% [87] and 72.8% [112]. We identified one study conducted among periodontal disease patients reporting a prevalence of 13.0% [113].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the 2009 H1N1 pandemic, the importance of having appropriate surveillance systems to monitor influenza trends became evident globally . However, there remains scarce information about the burden of influenza in the Eastern Mediterranean Region (EMR) …”
Section: Introductionmentioning
confidence: 99%